Decreased neuronal and increased endothelial fractalkine expression are associated with neuroinflammation in Parkinson’s disease and related disorders - Chu, Yaping; Harms, Ashley S.; Boehringer, Ashley; Kordower, Jeffrey H. (Frontiers in Cellular Neuroscience, 2025)
IntroductionChronic neuroinflammation is a persistent feature of individuals with Parkinson’s disease (PD). Dopaminergic neurodegeneration is partially associated with neuroinflammation. Neuron-to-microglia communication via fractalkine (CX3CL1) and its receptor plays a significant role in neuroinflammation. The relationship between fractalkine signaling and neuroinflammatory activities has been studied in animal models of PD, but its role is unclear in human PD. The current study aimed to elucidate the neuron–microglia communication between neuronal and endothelial fractalkine ligand expression, microglial activity, and CD4+ T cell infiltration during PD development.MethodsBrain sections were obtained from age-matched control subjects with no motor deficits (control, n = 8), mild motor deficits with nigral Lewy bodies (MMD-LB, n = 8) without a clinical diagnosis of PD, individuals with a clinical diagnosis of sporadic PD (n = 13), and progressive supranuclear palsy patients (PSP, n = 9). We performed quantitative stereological analyses and optical metrology of fractalkine expression in neurons and endothelial cells, and immunoreactivities of microglial and CD4+ T cells within the substantia nigra of PD cases. These data were compared with findings seen in age-matched controls as well as MMD-LB and PSP.ResultsIn PD, MMD-LB, and PSP postmortem brains, fractalkine expression in remaining nigral neurons was significantly reduced but markedly increased in blood vessel endothelial cells. The density of microglia and CD4+ T cells in the substantia nigra was significantly higher in these disorders when compared to controls. The decline in neuronal fractalkine expression was inversely correlated with increases in microglial numbers in the substantia nigra, while higher levels of fractalkine in endothelial cells were positively correlated with CD4+ cells infiltrating the injured substantia nigra across groups. Both PD and PSP groups displayed a similar pattern of neuroinflammatory changes.DiscussionThe downregulation of neuronal fractalkine expression caused by protein inclusions, such as abnormal alpha-synuclein or tau, is linked to microglia activation. When activated, microglia release cytokines that further stimulate endothelial cells to express fractalkine. This process recruits peripheral T cells, which infiltrate the injured brain. These findings indicate that the varying levels of neuronal and endothelial fractalkine expression in the substantia nigra contribute to neuroinflammatory activity in both synucleinopathy and tauopathy.